2018
DOI: 10.1111/eos.12580
|View full text |Cite
|
Sign up to set email alerts
|

Eikenella corrodens lipopolysaccharide stimulates the pro‐atherosclerotic response in human coronary artery endothelial cells and monocyte adhesion

Abstract: Eikenella corrodens is a gram‐negative bacterium, and although primarily associated with periodontal infections or infective endocarditis, it has been identified in coronary atheromatous plaques. The effect of its lipopolysaccharide (LPS) on human coronary artery endothelial cells (HCAECs) is unknown. Our aim was to examine the mechanism underlying the inflammatory response in HCAECs stimulated with E. corrodens‐LPS and to evaluate monocyte adhesion. Endothelial responses were determined by measuring the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Similarly, we showed that HCAECs in both 2D and 3D models exhibit an innate inflammatory cellular response to Aa‐LPS that might be related to the adhesion of monocytes. This response is similar to that induced in HCAECs by LPS from E. corrodens (Viafara‐Garcia et al, ) . Therefore, these results suggest that oral pathogens other than P. gingivalis strains have the capacity to induce proatherosclerotic endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similarly, we showed that HCAECs in both 2D and 3D models exhibit an innate inflammatory cellular response to Aa‐LPS that might be related to the adhesion of monocytes. This response is similar to that induced in HCAECs by LPS from E. corrodens (Viafara‐Garcia et al, ) . Therefore, these results suggest that oral pathogens other than P. gingivalis strains have the capacity to induce proatherosclerotic endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 84%
“…Evaluation of the adhesion of THP‐1 monocytes (ATCC ® ) to cultured HCAECs was carried out following a previously described procedure (Viafara‐Garcia et al, ). The 3D and 2D cultures were established by seeding 2 × 10 4 HCAECs on type I collagen scaffolds or in 96‐well plates, respectively, and incubating (5% CO 2 , 37°C) until cell confluence was reached.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…E. corrodens is among the bacteria frequently isolated from subgingival pockets in patients with severe periodontitis (Puig‐Silla, Montiel‐Company, Dasi‐Fernandez, & Almerich‐Silla, ). In an in vitro study, lipopolysaccharide of E. corrodens was proven to induce a pro‐atherosclerotic endothelial response and enhancing monocyte adhesion via toll‐like receptor 4, extracellular signal‐regulated kinase, and nuclear factor‐κB and p65 (Viafara‐Garcia, Gualtero, Avila‐Ceballos, & Lafaurie, ). This would imply that E. corrodens contribute to promote the atherosclerotic process by triggering endothelial inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the mechanisms used by periodontal pathogenic bacteria to damage the cardiovascular arterial endothelium. Human coronary artery endothelial cells (HCAECs) stimulated in vitro with lipopolysaccharide (LPS) or periodontopathogenic bacteria induce the secretion of cytokines and chemokines that favor the adhesion of monocytes to the activated endothelium (Gualtero et al, 2017;Viafara-Garcia et al, 2018).…”
Section: Introductionmentioning
confidence: 99%